Analysis on Gold Nanorod Interdigitated Elecrtrode Sensor Using Simple Photolithograpic Process. Issue 1 (February 2020) - Adam, Hussaini; Subash Gopinath, C. B.; Uda, M. N. A.; Hashim, Uda; Adam, Tijjani; Afnan Uda, M. N.
Abstract: With the higher demand of preventative healthcare in order to minimize costs and improve healthcare systems, the development and enhancement of sensor technology is vital. It is essential to develop a diagnostic device that can minimize time and lower task in testing, and can effectively reduce manufacturing and delivery costs because of portability of its designs. Here, we briefly describe the fabrication of aluminum interdigitated electrodes and deposition of gold nanorod on the fabricated microelectrode that can detect changes on the modified surface of the aluminum interdigitated electrode. Electrodes made from aluminum was employed for the fabrication because it is the most widely used electrode. Gold nanorod was deposited on the desired surface in order to enhance an enzymatic Response. The use of gold nanorod also enhances the sensitivity of detection due to the decrease of the thickness of probed zone. A simple and facile method for the deposition of gold nanorod colloid was described via a simple photolithographic technique on the interdigitated electrode (IDE). The gold nanoparticles pattern deposition on IDE was investigated by high power microscope (HPM), 3D Profilometer, and atomic force microscope (AFM).